2013
DOI: 10.2176/nmc.53.163
|View full text |Cite
|
Sign up to set email alerts
|

Cilostazol Reduces Periprocedural Hemodynamic Depression in Carotid Artery Stenting

Abstract: The clinical effects of two different types of antiplatelet drugs, cilostazol and thienopyridine drugs, were compared in patients treated by carotid artery stenting (CAS). Two hundred patients scheduled for CAS were randomized to either cilostazol or a thienopyridine drug (ticlopidine or clopidogrel). The study was conducted in open-label design. Aspirin was also given to all patients. All episodes of periprocedural hemodynamic instability (bradycardia, hypotension) were recorded together with all instances of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 30 publications
0
11
0
Order By: Relevance
“…Several studies have concluded that it reduces hypotension and bradycardia during CAS, thus preventing possible complications. 17,48 After analyzing 5 studies with reported 30-day outcomes, we found that the pooled MI/stroke/death rate reached only 3.1%, although 4 trials with reported late events indicated a pooled late rate of 7.9%. In one of the largest registries for CAS, Sakai et al 49 reported the incidence of first adverse events in a cohort of 934 patients undergoing CAS in Japan.…”
Section: Discussionmentioning
confidence: 92%
See 4 more Smart Citations
“…Several studies have concluded that it reduces hypotension and bradycardia during CAS, thus preventing possible complications. 17,48 After analyzing 5 studies with reported 30-day outcomes, we found that the pooled MI/stroke/death rate reached only 3.1%, although 4 trials with reported late events indicated a pooled late rate of 7.9%. In one of the largest registries for CAS, Sakai et al 49 reported the incidence of first adverse events in a cohort of 934 patients undergoing CAS in Japan.…”
Section: Discussionmentioning
confidence: 92%
“…The basic characteristics of all included patients are presented in Table 2 Four studies [17][18][19]21 were identified to compare basic characteristics between patients treated with cilostazol and those not. The pooled subanalysis of these studies found the groups relatively similar except for dyslipidemia and the use of open cell stents (Table 3).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations